Examining The Interrelationships Between Technology Acceptance, AI-Based Tools Usage, And Technology-Based Tutoring Systems And Their Impact: A Study Of Higher Education Institution In Lucknow - Marwah, Runita Sahai; Gupta, Bineet Kumar; verma, Satya Bhushan; Mishra, Ratnartuh; Kumar, Neeraj; waris, Saiyed Faiayaz (Journal of Neonatal Surgery, 2025)
The integration of technology into education has ushered in a new era of learning and teaching, with AI-based tools emerging as potential game-changers. Understanding how these tools are accepted, used, and impact student outcomes and organizational performance is crucial for maximizing their potential benefits. This study investigate the interrelationships between technology acceptance, the level of use of AI-based tools, and the adoption of technology-based tutoring systems, student performance and organizational performance. Using a research survey design and employing quota sampling technique, primary data was collected from a sample of 546 students from Lucknow-based Higher Education Institutions using a structured Likert scale questionnaire. Data was gathered over three months (March-May 2024) via Google Forms. The instrument's validity and reliability were established. Data analysis involved frequency, descriptive, correlation, and regression analyses using SPSS 25. The results showed that Technology acceptance significantly influences AI tool usage and technology-based tutoring, both of which positively impact student performance. Improved student performance subsequently contributes to enhanced organizational outcomes